(-6x-z)-(3y+(7x-(3z+8y+x)))=

Simple and best practice solution for (-6x-z)-(3y+(7x-(3z+8y+x)))= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6x-z)-(3y+(7x-(3z+8y+x)))= equation:


Simplifying
(-6x + -1z) + -1(3y + (7x + -1(3z + 8y + x))) = 0

Remove parenthesis around (-6x + -1z)
-6x + -1z + -1(3y + (7x + -1(3z + 8y + x))) = 0

Reorder the terms:
-6x + -1z + -1(3y + (7x + -1(x + 8y + 3z))) = 0
-6x + -1z + -1(3y + (7x + (x * -1 + 8y * -1 + 3z * -1))) = 0
-6x + -1z + -1(3y + (7x + (-1x + -8y + -3z))) = 0

Combine like terms: 7x + -1x = 6x
-6x + -1z + -1(3y + (6x + -8y + -3z)) = 0

Remove parenthesis around (6x + -8y + -3z)
-6x + -1z + -1(3y + 6x + -8y + -3z) = 0

Reorder the terms:
-6x + -1z + -1(6x + 3y + -8y + -3z) = 0

Combine like terms: 3y + -8y = -5y
-6x + -1z + -1(6x + -5y + -3z) = 0
-6x + -1z + (6x * -1 + -5y * -1 + -3z * -1) = 0
-6x + -1z + (-6x + 5y + 3z) = 0

Reorder the terms:
-6x + -6x + 5y + -1z + 3z = 0

Combine like terms: -6x + -6x = -12x
-12x + 5y + -1z + 3z = 0

Combine like terms: -1z + 3z = 2z
-12x + 5y + 2z = 0

Solving
-12x + 5y + 2z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-12x + 5y + -5y + 2z = 0 + -5y

Combine like terms: 5y + -5y = 0
-12x + 0 + 2z = 0 + -5y
-12x + 2z = 0 + -5y
Remove the zero:
-12x + 2z = -5y

Add '-2z' to each side of the equation.
-12x + 2z + -2z = -5y + -2z

Combine like terms: 2z + -2z = 0
-12x + 0 = -5y + -2z
-12x = -5y + -2z

Divide each side by '-12'.
x = 0.4166666667y + 0.1666666667z

Simplifying
x = 0.4166666667y + 0.1666666667z

See similar equations:

| (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y |

Equations solver categories